Investigating the effects of humorous video on students' anxiety, enjoyment, and engagement - Kuncoro, Adhityo; Anam, Syafiul; Munir, Ahmad (LITERA, 2024)
Studies on the use of humorous videos in educational settings especially on informatics engineering study program is still less explored. This study focuses on investigating the effects of humorous videos and students' perceptions of this intervention in the EFL classroom. Fifty participants are from the informatics engineering study program. This study used a one-group pretest-post-test design to collect quantitative data, with the same independent variable measured in a group of participants before and after treatment. This study found that, first, humorous video has no significant effect in statistics to increase enjoyment, engagement, and reduce anxiety in informatics study program students. Other findings found that, second, students have positive perception towards the use of humorous videos in English lesson. They share a lot of benefits of using humorous videos in English lesson such as in promoting enjoyable and relax learning environment, reducing anxiety, build confidence, influence new perspective on making errors, and so on.